Predictors of hypertension awareness, treatment and control in South Africa: results from the WHO-SAGE population survey (Wave 2) - Lisa Jayne Ware (2018)
© 2018, Springer Nature Limited. South Africa has one of the highest levels of hypertension globally, coupled with poor rates of diagnosis, treatment and control. Risk factors that predict hypertension in high income countries may perform differently in the African context, where communicable disease, obesity and malnutrition co-exist. This study investigated traditional risk factors alongside other health and sociodemographic indicators to determine predictors of hypertension prevalence and management. Participants were recruited from households across South Africa as part of WHO’s Study on global AGEing and adult health (WHO SAGE) Wave 2 (2015). Blood pressure (BP) was measured in triplicate and sociodemographic and health data collected by survey (n = 1847; 30% 18–39 years, 39% 40–59 years, 31% 60 years+; median age 51 years; 68% female). Of all adults, 43% were hypertensive (n = 802), of which 58% (n = 398) were unaware, 33% (n = 267) were on medication, with only 18% (n = 141) controlled on medication (BP < 140/90 mmHg). Multivariate logistic regression showed waist-to-height ratio > 0.5 and diabetes comorbidity were the most significant predictors of hypertension presence, awareness and treatment. Individuals with diabetes were twice as likely to have hypertension, 7.0 times more likely to be aware, 3.3 times more likely to be on antihypertensive medication, and 2.4 times more likely to be controlled on medication. Women and individuals reporting lower salt use were more likely to be aware and treated for hypertension. Applying the 2017 AHA/ACC hypertension guidelines showed only 1 in 4 adults had normal BP. As with HIV, similarly intensive efforts are now needed in the region to improve non-communicable disease diagnosis and management.